Codification of theories of organizational learning dimensions for further use in the VUCA hotel businesses environment evolving to BANI - Kakarougkas, Christos (International Conference on Business and Economics - Hellenic Open University, 2025)
The recent consecutive crises and technological, geopolitical, and trade developments have forced the business environment in which hotel businesses operate to evolve from VUCA: Volatile, Uncertain, Complex, and Ambiguous to BANI: Brittle, Anxious, Non-Linear, Incomprehensible. To effectively respond to the impact of the VUCA to BANI evolution, hotel businesses need to adjust their operations. This adaptation requires human resources to acquire new knowledge and skills to help hotel businesses evolve in the BANI environment. This study, through qualitative latent content analysis of the findings of previous scientific research, synthesizes and highlights elements of organizational learning dimensions theories, which will help human resources of hotel businesses, respond to the challenges of the VUCA to BANI business environment on operational and strategic levels. The results of this study present original and valuable scientific and practical insights for further use by researchers and managers in the hospitality field. JEL Classifications: M54 Keywords: organizational learning dimensions, hotels, VUCA to BANI, business environment evolution